Fluorophore‐Labeled Cyclic Nucleotides as Potent Agonists of Cyclic Nucleotide‐Regulated Ion Channels. (4th May 2020) - Lelle, Marco; Otte, Maik; Bonus, Michele; Gohlke, Holger; Benndorf, Klaus
Abstract: High‐affinity fluorescent derivatives of cyclic adenosine and guanosine monophosphate are powerful tools for investigating their natural targets. Cyclic nucleotide‐regulated ion channels belong to these targets and are vital for many signal transduction processes, such as vision and olfaction. The relation of ligand binding to activation gating is still challenging, and there is a need for fluorescent probes that enable the process to be broken down to the single‐molecule level. This inspired us to prepare fluorophore‐labeled cyclic nucleotides, which are composed of a bright dye and a nucleotide derivative with a thiophenol motif at position 8 that has already been shown to enable superior binding affinity. These bioconjugates were prepared by a novel cross‐linking strategy that involves substitution of the nucleobase with a modified thiophenolate in good yield. Both fluorescent nucleotides are potent activators of different cyclic nucleotide‐regulated ion channels with respect to the natural ligand and previously reported substances. Molecular docking of the probes excluding the fluorophore reveals that the high potency can be attributed to additional hydrophobic and cation‐π interactions between the ligand and the protein. Moreover, the introduced substances have the potential to investigate related target proteins, such as cAMP‐ and cGMP‐dependent protein kinases, exchange proteins directly activated by cAMP or phosphodiesterases. Abstract : Selecting channels : Fluorescent cyclic nucleotide derivatives synthesized with a thiophenol motif‐containing heterobifunctional cross‐linking reagent efficiently activate CNG as well as HCN channels in the nanomolar range and are potential candidates to study related target proteins.